The Impact of Wealth on the Amount and Quality of Child Labor - Del Carpio, Ximena V. (2012)
This paper analyzes to what extent, and under what conditions, an increase in household wealth affects the use of child labor in poor households. It develops a simple theoretical model, which uses child labor, training, and schooling to maximize household income over time, subject to resource constraints. Then, it conducts an empirical analysis using randomized trial data, which were collected for the evaluation of the 2006 Nicaragua conditional cash transfer program. This social program transfers wealth to poor families in rural areas, conditional on children's school attendance and health check-ups. In addition, for one third of the beneficiaries, there is a further wealth transfer to start a non-agricultural business. The paper finds that the conditional cash transfer program affected the volume and quality of child labor, reducing it in the aggregate and steering it towards skill-forming activities. Specifically, the program appears to have reduced the use of child labor for household chores and farm work, while increasing it for the non-traditional, skill-forming activities related to commerce and retail. Moreover, the paper finds that the source behind the increase in skill-forming child labor is not the basic component, which provides a transfer for paying for schooling and health services, but it's the business-grant component, which provides a household grant for the creation of a micro business or a new economic activity.